Metal ecotoxicology : (Lewis Publishers, 1991)
This book provides an in-depth discussion of various aspects of metal ecotoxicology. State-of-the-art information and techniques in areas ranging from metal behavior in surface waters to bioaccumulation kinetics and toxicokinetics to community effects are presented in a hierarchical arrangement. Specific topics discussed include metals in abiotic components of ecosystems, autecology (effects of metals relative to the individual or a single species), and metals in marine and freshwater systems in the context of synecology (species associated and interacting as a unit). This is an important book that will be useful to researchers, risk assessment consultants, regulatory personnel, and teachers and students.